2011 Triennial Surveillance Review : Staff Background Studies. (Policy Papers; Policy Paper, 2011)
This paper evaluates the IMF's exchange rate analysis since the 2008 TSR. It focuses on the evolution of methods, the quality of the IMF's multilateral and bilateral exchange rate analysis, the evenhandedness and transparency of this analysis, and the need to improve the coverage and integration of external stability assessments.